Tourism Development Strategy of Flory Village in Yogyakarta in the Face of the Covid-19 Pandemic - Dessy Rachmawatie; Faisal Ramadhan (Jurnal Ekonomi, Manajemen, Akuntansi dan Keuangan, 2025)
This study aims to analyse the development strategy of Kampung Flory Tourism Village in Yogyakarta, Indonesia, in responding to post-pandemic challenges. A qualitative descriptive approach was applied, supported by SWOT (Strengths, Weaknesses, Opportunities, and Threats) analysis. Data were collected through observations, in-depth interviews, and questionnaires involving 100 tourists selected using incidental sampling. The findings reveal that Kampung Flory has strong internal capabilities, with an IFAS score of 3.115, where strengths (2.084) outweigh weaknesses (1.031). Key strengths include environmental quality, adequate facilities, and digital promotion. The EFAS score of 2.722 indicates that opportunities (2.056) exceed threats (0.667), driven by increasing demand for nature-based tourism, technological advancement, and accessibility. The SWOT matrix positions Kampung Flory in Quadrant I, indicating a growth-oriented strategy. Strategic priorities include environmental conservation, optimisation of digital marketing, tourism product innovation, and service quality improvement. These strategies are essential to enhance destination resilience and competitiveness in the post-pandemic era. This study contributes to community-based tourism and crisis management literature by highlighting the importance of leveraging internal strengths to capitalise on emerging tourism trends.